Tests of carbon targets for 12C+12C reactions at astrophysical energies. (22nd January 2015) - Morales-Gallegos, L; Aliotta, M; Di Leva, A; Gialanella, L; Schürmann, D; De Cesare, M; Davinson, T; Imbriani, G; Romano, M; Romoli, M
Abstract: As a preliminary step towards measurements of the 12 C + 12 C reactions at astrophysical energies, we investigate the behaviour of targets under beam bombardment, specifically the quantitative relation between hydrogen and deuterium content of different carbon targets and target temperature. Experiments have taken place at the CIRCE accelerator in Caserta, Italy and preliminary results are presented here.